The Impact of Implementing PSAK 116 on the Financial Performance of Transportation Sub-Sector Companies Listed on the Indonesian Stock Exchange - Mardiani, Rika; Sugiharti, Harpa; Hardiana, R. Dian; Muntashofi, Badria (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
The process of aligning Indonesian accounting standards with International Financial Reporting Standards (IFRS) is currently ongoing in Indonesia. On January 1, 2020, Indonesia implemented PSAK 73 (currently Named PSAK.116) , an adaptation of IFRS 16 specifically for lease accounts. The adoption of this PSAK profoundly impacts companies that primarily acquire their assets through lease arrangements. Conversely, numerous firms in the Transportation Sub Sector in Indonesia often use leasing as a means of obtaining their assets. Additionally, it includes four measured financial ratios: solvency ratio, profitability ratio, liquidity ratio, and bankruptcy risk. This study employs quantitative descriptive research methodologies, applying financial report data from transportation companies The data covers the years 2017 until 2019, representing the period before to the implementation of PSAK 116. Additionally, data from the years 2020 until 2022 is included to represent the period of PSAK 116 implementation. The findings of this study indicate that there are not significant differences in solvency ratios, profitability ratios, liquidity ratios and bankruptcy risk before and after the adoption of PSAK 116 in transportation sub-sector companies listed on the Indonesia Stock Exchange. Consequently, the adoption of PSAK 116 is unlikely to result in significant changes to the Company's financial statements.